Unraveling the potential of zinc protoporphyrin-forming lactic acid bacteria for replacing nitrite and their role in quality characteristics of Harbin dry sausage - Qianhui Yang; Zhiqiang Feng; Yaru Yuan; Xiufang Xia; Qian Liu; Qian Chen; Baohua Kong (Food Chemistry: X)
This study evaluated the effects of zinc protoporphyrin-producing lactic acid bacteria specifically Weissella viridescens JX11, Weissella viridescens MDJ8, and Lactobacillus pentosus Q on nitrite substitution and the quality characteristics of Harbin dry sausage. The redness (a*) values in the bacteria-inoculated groups were significantly higher than those in the control group (P < 0.05) during fermentation. Bacteria-inoculated sausages exhibited a higher proportion of oxymyoglobin and a lower proportion of metmyoglobin (P < 0.05). Ferrochelatase activity in the inoculated groups was significantly higher than in the control at days 3 and 6 (P < 0.05). Additionally, the fluorescence intensity of zinc protoporphyrin and its precursor, protoporphyrin IX, in the bacteria-inoculated groups significantly increased during fermentation (P < 0.05), and W. viridescen JX11 exhibited the highest fluorescence intensity and UV–Vis absorption peak (P < 0.05). These results suggest that zinc protoporphyrin-producing lactic acid bacteria could potentially replace nitrite in fermented dry sausages.